2021
DOI: 10.3390/app11125505
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Specific Loss Power and Heating Temperature in CoFe2O4 Nanoparticles as Possible Candidate for Alternative Cancer Therapy by Superparamagnetic Hyperthemia

Abstract: In this paper, we present a theoretical study on the maximum specific loss power in the admissible biological limit (PsM)l for CoFe2O4 ferrimagnetic nanoparticles, as a possible candidate in alternative and non-invasive cancer therapy by superparamagnetic hyperthermia. The heating time of the nanoparticles (Δto) at the optimum temperature of approx. 43 °C for the efficient destruction of tumor cells in a short period of time, was also studied. We found the maximum specific loss power PsM (as a result of superp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 81 publications
2
12
0
Order By: Relevance
“…The results obtained depending on the frequency show a shift of the maximum specific loss power towards smaller values of the nanoparticles diameter, respectively from 18.1 nm to 16.2 nm, when the frequency of the magnetic field increases in the range 100-500 kHz (Figure 9a), simultaneously with the almost linear increase of the maximum specific loss power (Figure 9b). A similar variation in the diameter of nanoparticles DM was observed both in the case of F3O4 nanoparticles [37] and in the case of CoFe2O4 nanoparticles [52]. However, in the case of Fe3O4 nanoparticles coated with γ-CDs it is found that there is a difference between the diameter values corresponding to the maximum specific loss power compared with the case of Fe3O4 nanoparticles, a difference that increases as the frequency decreases at 100 kHz.…”
Section: The Effect Of the Magnetic Field Frequencysupporting
confidence: 72%
See 2 more Smart Citations
“…The results obtained depending on the frequency show a shift of the maximum specific loss power towards smaller values of the nanoparticles diameter, respectively from 18.1 nm to 16.2 nm, when the frequency of the magnetic field increases in the range 100-500 kHz (Figure 9a), simultaneously with the almost linear increase of the maximum specific loss power (Figure 9b). A similar variation in the diameter of nanoparticles DM was observed both in the case of F3O4 nanoparticles [37] and in the case of CoFe2O4 nanoparticles [52]. However, in the case of Fe3O4 nanoparticles coated with γ-CDs it is found that there is a difference between the diameter values corresponding to the maximum specific loss power compared with the case of Fe3O4 nanoparticles, a difference that increases as the frequency decreases at 100 kHz.…”
Section: The Effect Of the Magnetic Field Frequencysupporting
confidence: 72%
“…This difference obtained in the case of bionanoparticles of Fe3O4-γ-CDs is due to the presence of the organic layer of CDs at the surface of the nanoparticles, which contributes through its thickness to the hydrodynamic diameter and implicitly to the Brown relaxation mechanisms. As a result, the maximum specific loss power shifts to A similar variation in the diameter of nanoparticles D M was observed both in the case of F 3 O 4 nanoparticles [37] and in the case of CoFe 2 O 4 nanoparticles [52]. However, in the case of Fe 3 O 4 nanoparticles coated with γ-CDs it is found that there is a difference between the diameter values corresponding to the maximum specific loss power compared with the case of Fe 3 O 4 nanoparticles, a difference that increases as the frequency decreases at 100 kHz.…”
Section: The Effect Of the Magnetic Field Frequencysupporting
confidence: 65%
See 1 more Smart Citation
“…With precise delivery of microwave radiation to the desired place, localization of hyperthermia to the pathological site is possible. Among the magnetic nanoparticles, due to the magnetic properties and efficiency in energy dissipation (in this case, the conversion of magnetic energy into thermal energy), the most promising seems to be magnetite-based (Fe 3 O 4 ) [ 105 ]. There are also other significant features of Fe 3 O 4 nanoparticles that can be used in treatment.…”
Section: Hyperthermiamentioning
confidence: 99%
“…Nevertheless, Fe 3 O 4 NPs are usually coated with different hydrophilic layers to ensure a lack of interactions between the nanoparticles (van der Waals and magnetic dipole-dipole, which lead to agglomerates) and the colloidal stability [ 7 ]. Fe 3 O 4 ferrimagnetic nanoparticles smaller than 30–50 nm have been found to be targeted for magnetic hyperthermia and superparamagnetic hyperthermia [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], but many other studies have been carried out to find other suitable ferrimagnetic nanoparticles or those more suitable than magnetite, both in terms of thermal efficiency and cell toxicity [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Research in this field has also focused on ferromagnetic nanoparticles [ 31 , 32 ], with special attention given to Fe nanoparticles, which in terms of efficiency of loss power and heating would be most suitable due to their high magnetization and initial susceptibility [ 33 ] compared to ferrimagnetic nanoparticles [ 34 ].…”
Section: Introductionmentioning
confidence: 99%